Genome-wide identification of XsDGAT family and their expression patterns in yellowhorn (Xanthoceras sorbifolium) - Guan Liu; Hanhui Wang; Dongye Zhang; Yanan Lu; Song Yu; Changhua Liu (Biotechnology & Biotechnological Equipment)
Diacylglycerol acyltransferase (DGAT) plays a pivotal role in lipid metabolism, particularly in the biosynthesis of triacylglycerols (TAGs), which are essential for energy storage and cellular membrane formation. Xanthoceras sorbifolium, commonly known as yellowhorn, is notable for the high oil content of its seeds and its potential in biodiesel production. However, its DGATs have not been thoroughly studied. In this study, we conducted the bioinformatics analysis of the XsDGAT gene family in X. sorbifolium. The XsDGAT homologs, sequence features, domain architecture, and evolutionary relationships were identified, the expression patterns across different tissues and their potential regulatory elements of XsDGATs were also displayed, providing valuable insights into their potential roles in lipid biosynthesis and accumulation. This comprehensive bioinformatics analysis offers valuable resources for further experimental investigations and potential applications aimed at enhancing lipid productivity in X. sorbifolium.